2021
DOI: 10.3390/polym13244323
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Engineered Biomaterials and Magnetite on Wastewater Treatment: Biogas and Kinetic Evaluation

Abstract: In this study, the principle of sustaining circular economy is presented as a way of recovering valuable resources from wastewater and utilizing its energy potential via anaerobic digestion (AD) of municipality wastewater. Biostimulation of the AD process was investigated to improve its treatability efficiency, biogas production, and kinetic stability. Addressing this together with agricultural waste such as eggshells (CE), banana peel (PB), and calcined banana peels (BI) were employed and compared to magnetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Carbon (30.23 to 64.31 percent C), oxygen (22.67 to 43 percent O), sulphur (0.82 to 13.1 percent S), chlorine (0.80 to 15.68 percent Cl), and iron (7.04 to 67.32 percent Fe) were also shown to be the most prevalent elements in all MCs. This is consistent with Equation (1), which demonstrated that magnetite is predominantly composed of Fe and O, while the addition of extra components (S and Cl) may enhance their surface area, allowing for improved biosorption and reusability [ 35 ]. In addition to the elements listed above, the RF and CF included potassium (0.35 to 2.14 percent K) and sodium (1.67 to 6.37 percent Na), respectively.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Carbon (30.23 to 64.31 percent C), oxygen (22.67 to 43 percent O), sulphur (0.82 to 13.1 percent S), chlorine (0.80 to 15.68 percent Cl), and iron (7.04 to 67.32 percent Fe) were also shown to be the most prevalent elements in all MCs. This is consistent with Equation (1), which demonstrated that magnetite is predominantly composed of Fe and O, while the addition of extra components (S and Cl) may enhance their surface area, allowing for improved biosorption and reusability [ 35 ]. In addition to the elements listed above, the RF and CF included potassium (0.35 to 2.14 percent K) and sodium (1.67 to 6.37 percent Na), respectively.…”
Section: Resultssupporting
confidence: 84%
“…To begin, 1 L stock solutions were calculated for each chemical using their mass (g) and molecular weights, as indicated in Table 2 . In reality, the 0.4 M Fe 3+ , 0.2 M Fe 2+ , and 3 M NaOH stock solutions were made using 108.12 g, 55.61 g, and 199.99 g dissolved in 1 L distilled water, respectively [ 35 ]. These were calculated using the Sigma-Aldrich mass molarity calculator with a known concentration and volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characterised distribution (Table 1) of the wastewater was outsourced from a local eThekwini municipal wastewater treatment plant in the KwaZulu-Natal province, South Africa. A magnetite-titanium photocatalyst (Fe-TiO 2 ) synthesised via the co-precipitation technique reported in our previous works [21,37] was used. Additional characterisation with the Brunauer-Emmett-Teller theory (Micromeritics, TriStar II Plus, Norcross, GA, USA) recorded a BET surface area of 62.73 m 2 /g, pore volume of 0.017 cm 3 /g and particle size of 1.337 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The results obtained are shown in Table 1 . The nanomaterials used in this study was synthesized using the co-precipitation synthesis method, which has been detailed in studies by Tetteh, et al [ 28 ], Amo-Duodu, et al [ 29 ], and Amo-Duodu, et al [ 30 ]. The characteristics of the nanomaterials have been reported in these studies.…”
Section: Methodsmentioning
confidence: 99%